Compressive strength and microstructure of assorted wastes incorporated geopolymer mortars: Effect of solution molarity - Huseien, G.; Ismail, Mohamed; Khalid, N.; Hussin, M.; Mirza, J. (Elsevier, 2018)
© 2018 Faculty of Engineering, Alexandria University This paper presents the solution molarity dependent microstructures and mechanical properties of multi-blend geopolymer mortars (GPMs). Geopolymer mortars were cured at ambient temperature under varying concentration (from 2 to 16 M) of sodium hydroxide (NH) solution. GPMs are by conducting mechanical tests such as compressive, split tensile and flexural strengths and characterised by microstructural studies, such as X-ray diffraction (XRD), scanning electron microscopy (SEM) and X-ray spectroscopy (EDS). The effect of Na2O, H2O content, solution modulus (SiO2:Na2O) and Na2O:Al2O3 on GPMs strength were determined. The flow ability and setting time of such GPMs found to decrease linearly with increasing alkali concentration. Conversely, the GPMs comprehensive, split tensile and flexural strengths and the density are enhanced with increasing alkali concentration. Samples activated with 12 M NH solution are most strongly affected by silica dissolution. Furthermore, the ratio of (Na2O:Al2O3) was demonstrated to influence the compressive strength significantly and the (Na2O:Al2O3 = 0.84) presented the optimum strength.